Prognostic significance of hs-CRP in acute ischemic stroke patients - Pandey, Sonika; Kawre, K. K.; Dwivedi, P. (International Journal of Advances in Medicine, 2018)
Background: Stroke, a serious neurological disease is a major cause of death and disability throughout world. The pathophysiology of stroke involves inflammatory pathways, oxidative damage, apoptosis, angiogenesis and neuroprotection. High sensitivity C - reactive protein (hs-CRP) is associated with atherosclerosis and predict incident stroke in many patients. Objective of present study was to find out change in pattern of hs-CRP in acute ischemic stroke (AIS) patients during 3-months follow up and its prognostic significance. Methods: Single centre prospective cross-sectional time bound study. 256 were screened and 130 meet the inclusion and exclusion criteria, of which 100 gave informed consent and 80 patients completed the study at 3 months. Demographic, clinical parameters including NIHSS scoring, biochemical analysis was collected at enrolment, discharge and at end of the study. Results: hs-CRP levels in AIS increased significantly (within 24 hours of stroke) and continued to increase further at discharge, while decreased significantly during 3 months follow up. >7mg/dl hs-CRP at admission had 3.5 fold higher risk of mortality. Age >60 years, metabolic syndrome, hyperlipidemic, SBP >160mmHg and hs-CRP > 7 mg/dL increases relative risk in AIS stroke patients by 1.42, 1.09, 1.11, 1.577 and 3.23 fold respectively. Conclusions: hs-CRP increased significantly in AIS patients during 1st weeks of stroke with subsequent gradual decrease by the end of 3 months, the severity scoring system could determine prognosis on admission to ICU while hs-CRP is the main factor determining short as well as long term prognosis. We recommend serial measurements of hs-CRP for prognostication in AIS subjects.